Education on Normal and Caesarean Delivery Based on Leaflets and Animated Videos - R.A Wulandari; Sastrawan Sastrawan; Sismulyanto Sismulyanto; Lalu Sulaiman; Ni Putu Dian Ayu Anggraeni (Universitas Nurul Jadid, 2025)
The cesarean section (CS) rate in Mataram City has reached 67.2%, far above the national average. This increase raises medical, social, and economic concerns, especially since many procedures are performed without clear medical indications. A key contributing factor is low health literacy among women of reproductive age, including limited understanding of childbirth options, fear of pain, misconceptions about safety, and lack of family support. This community service activity applied a Participatory Action Research (PAR) approach in four stages: (1) problem identification with health centers, cadres, and women of reproductive age; (2) development of educational media in the form of leaflets and animated videos; (3) implementation through interactive lectures and discussions with 30 participants at Yarsi Mataram; and (4) participatory reflection and evaluation using pre–post tests. the findings showed an increase in average knowledge scores from 72.33 to 91.33. Beyond knowledge, participants also reported reduced fear of normal delivery, greater confidence in making childbirth decisions, and stronger commitment to seek support from health workers and families. This activity demonstrates that targeted health education can effectively improve both knowledge and attitudes toward childbirth. Replication is recommended in other areas with high CS rates, with cadres and community leaders trained as facilitators to ensure sustainability and wider impact.